Development of Scientific and Constructivism-Based Handouts on Social Arithmetic Materials - Lulu Hasibuan; Aulia Nugraha (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The purpose of this study is to combine a scientific approach and a constructivist learning model so that students can build their own knowledge through their experiences from the results of interactions with the environment using handout media. Methodology: In this research, development uses the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). The subject of this development trial was a mathematics teacher at school to respond to handout teaching materials, and the intended users of this product were class VII students of SMP N 11 Muaro Jambi. The type of data used is the type of quantitative data. Main Findings: This research has produced a printed teaching material product in the form of scientific and constructivism-based Handouts on social arithmetic material, which can facilitate students to play an active role in the learning process, as well as make it easy for students to understand the concept of subject matter. Based on the results of the research and discussion, it can be concluded as follows: The development of scientific and constructivism-based Handouts on social arithmetic material is carried out in several stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. Novelty/Originality of this study: The development of scientific and constructivism-based Handouts on social arithmetic material is carried out in several stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation.